Securlties Analysis and Portfolio Management. - Avadhani, V. A. (Himalaya Pub. House, 2009)
This book deals with the portfolio management for which Securities analysis is an essential ingredient. Securities are dealt with in the financial markets and in particular in the money and capital markets. These markets are subject to changes due to environmental forces and policy variations and a host of socio-economic factors. As these changes have to be incorporated in the book from time to time, these revisions are necessary to make it more student friendly. The present revision has taken care to see that all those developments are incorporated in the book and data and facts are according.